DEVELOPING STORYBOOK FOR ELEMENTARY SCHOOL IN LUBUKLINGGAU - Ayu Oktaviani; Dewi Syafitri; Berti Arimbi (Universitas Sarjanawiyata Tamansiswa, 2020)
The aim of this study was to find out the validity, practicality, and effectiveness of the developed storybook. Research and Development proposed by Branch (2009) consisting of analysis, design, development, implementation, and evaluation (ADDIE) was used in developing the product. In the evaluation phase, formative evaluation proposed by Tessmer (1993) consisting of experts review, there were three experts reviewing the product, namely content expert, media expert, and instructional design expert. Three students involved in the one-to-one evaluation, six students involved in the small group phase and eleven students in the field phase. To collect the data, questionnaires, interview, and a test was used. The collected data were analyzed qualitatively for the interview and quantitatively by using the average score for the questionnaires and percentage for the test. The developed product was valid after being evaluated in the expert review phase in terms of its content, media, and instructional design with an average score of 4.1 categorized as highly valid. The product was also practical with an average score of 4.6 in One-To-One and 4.0 in Small Group phase categorized as highly practical. The product was also had very high effectiveness which average score 91.2.Â